Structural integrity assessment in the construction of the Comuneros II Bridge: PIT test case study (ASTM D5882) on abutments - Ariza Flores, Victor Andre (2024)
This article presents the results of the pile integrity tests (PIT) according to the ASTM D5882 standard, carried out in the construction project of the Comuneros II Bridge in Huancayo, Peru. The main objective of these tests was to evaluate the structural integrity of the piles used in the bridge, identifying possible failures or damage along its shaft. Testing was conducted using a model FV "PIT Collector" manufactured by Pile Dynamics, Inc., and spanned multiple project locations, allowing for a comprehensive assessment of pile quality. The field services were carried out on July 26, 2022, and the detailed analyses were subsequently carried out in the office. The results obtained were analyzed to verify the consistency and reliability of the piles, providing a detailed view of their structural condition. In addition, the calibration certificates of the sensors used are presented, ensuring the accuracy and validity of the data collected. This study not only contributes to ensuring the safety and durability of the Comuneros II Bridge, but also provides a valuable reference for future structural integrity assessments on similar construction projects.